The Impact of Motivation and Work Environment on Employee Work Enthusiasm at Seongho Shipping - Samuel Andriano Nainggolan; Zaharuddin; I Gede Adiputra (Journal Informatic, Education and Management (JIEM), 2026)
The purpose of this research is to determine how much influence work motivation and work environment have on employee work enthusiasm, both partially and simultaneously at Seongho Shipping. The method used in this research is a quantitative research method with descriptive approach. The sampling technique used in this research is saturated sampling where the author takes all population as samples totaling 35 people, and the data analysis technique used is an analysis technique using data quality testing, simple linear regression analysis using SPSS version 25.0 application. Based on the analysis carried out, it can be concluded that the quality of the data on the variables of work motivation, work environment and work enthusiasm are valid and reliable significantly both partially and simultaneously, each or together can influence the work enthusiasm of Seongho Shipping employees.